Malnutrition and Anemia Prevalence in Adolescent Women of Nepal - Khanal, Prabha (Patan Prospective Journal, 2023)
Adolescents have seen a rise in the problem of malnutrition over many years. In adolescents, mainly girls have been seen to be more vulnerable than boys in the case of nutrition deficiency. Malnutrition is mainly caused due to eating and dietary habits among the concerned group. This study has tried to find the status of malnutrition among adolescent women aged 15–19 years based on secondary data from the Nepal Demographic and Health Survey (NDHS) in 2011, 2016, and 2022. This study found that 27 percent of adolescent girls are of short stature. The number has slightly increased in the past year. The percentage of obese people has been increasing as (0.3%, 0.4%, and 0.6%) in 2011, 2016, and 2022 respectively. Similarly, the prevalence of anemia in adolescent girls has been seen comparatively high, despite fluctuations in the trend appearing in three different surveys as (38.5%, 43.6%, and 39.4%) in 2011, 2016, and 2022 respectively. The anemia problem has mainly increased due to micronutrition deficiency among adolescent girls. Only 17 percent of adolescent women are taking iron and folic acid. To eradicate the level of malnutrition among adolescents, it is necessary to launch a broader nutritional program that should be focused on adolescents in community- and region-based malnutrition programs.